Аналіз правового регулювання міжбюджетних трансфертів - Астіон, Світлана Іванівна; Астион, Светлана Ивановна; Astion, Svetlana (Одеса : Юрид. л-ра, 2014)
The article deals with the characterization of institutional regulation of interbudgetary relations, the analysis of the regulation of interbudgetary transfers, and certain problems of legal regulation to enhance the financial autonomy of local governments.
Астіон С. І. Аналіз правового регулювання міжбюджетних трансфертів / С. І. Астіон // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 165-171.
Keywords: правове регулювання; міжбюджетні відносини; фінансова автономія; органи місцевого самоврядування; правовое регулирование; межбюджетные отношения; финансовая автономия; органы местного самоуправления; regulation; interbudgetary relations; fiscal autonomy; local self-government